Tourism Potential and Waste Management in Coastal Areas of Bengkulu City: Potensi Wisata Dan Pengelolaan Sampah di Wilayah Pesisir Kota Bengkulu - Yani, Ahmad; Purwanto, Agus; Romedia, Atra (Media Ilmiah Teknik Lingkungan (MITL), 2025)
This study uses strategic management to uncover emerging issues intensively and comprehensively. This study aims to determine what efforts have been made to improve and maximize existing resources so that they can be used in the development of coastal tourism and what obstacles arise in coastal tourism objects in Bengkulu City. The focus of this study is on the strategy for improving the tourism sector, especially coastal tourism, as the main instrument for measuring the environment and obtaining strategies for strengths, weaknesses, opportunities and threats needed in the planning process for developing and developing coastal tourism. The conclusion of this study is based on the strategy for developing coastal tourism in Bengkulu City carried out by the Bengkulu City Tourism Office, there are still indicators that have not been successful, as seen from the uneven distribution of development in several leading destinations and the lack of foreign tourists visiting. One of the problems in the coastal area is waste management. Waste can cause environmental problems if its existence is not handled properly. Based on the results of this data collection, several strategies for waste management in the coastal area of ​​Panjang Beach in Bengkulu City are presented, namely storage, collection, transportation, processing, final processing, financing institutions, regulations.